2012
DOI: 10.1051/0004-6361/201118029
|View full text |Cite
|
Sign up to set email alerts
|

Herschel/PACS spectroscopy of NGC 4418 and Arp 220: H2O, H218O, OH,18OH, O I, HCN, and NH3

Abstract: Full range Herschel/PACS spectroscopy of the (ultra)luminous infrared galaxies NGC 4418 and Arp 220, observed as part of the SHINING key programme, reveals high excitation in H 2 O, OH, HCN, and NH 3 . In NGC 4418, absorption lines were detected with E lower > 800 K (H 2 O), 600 K (OH), 1075 K (HCN), and 600 K (NH 3 ), while in Arp 220 the excitation is somewhat lower. While outflow signatures in moderate excitation lines are seen in Arp 220 as have been seen in previous studies, in NGC 4418 the lines tracing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
166
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(200 citation statements)
references
References 111 publications
(138 reference statements)
33
166
1
Order By: Relevance
“…With the data at hand it is difficult to separate the two suggested models for CO emission, and we suggest the two interpretations as two equally probable scenarios. Both interpretations are consistent with the molecular inflow detected by González-Alfonso et al (2012) with Herschel observations (see discussion in Sect. 4.3).…”
Section: Outflow/in-flow Scenariosupporting
confidence: 90%
See 1 more Smart Citation
“…With the data at hand it is difficult to separate the two suggested models for CO emission, and we suggest the two interpretations as two equally probable scenarios. Both interpretations are consistent with the molecular inflow detected by González-Alfonso et al (2012) with Herschel observations (see discussion in Sect. 4.3).…”
Section: Outflow/in-flow Scenariosupporting
confidence: 90%
“…A spherical molecular in-flow in the core of NGC 4418 was first suggested by González-Alfonso et al (2012) to explain the redshifted OH absorption observed by the Herschel satellite. The presence of an atomic and molecular in-flow in NGC 4418 would not be surprising.…”
Section: Atomic and Molecular In-flowmentioning
confidence: 92%
“…Herschel PACS observations by González-Alfonso et al (2012), and our combined MERLIN/SMA study ) reveal the presence of redshifted OH and HI absorption, which is interpreted as the signature of a molecular inflow. The presence of a molecular outflow is also suggested by a U-shaped red optical feature along the northwestern semi-minor axis of the galaxy .…”
Section: Ngc 4418: the Prototypical Obscured Lirgmentioning
confidence: 52%
“…A compact IR source of similar temperature and size is also required by models by González-Alfonso et al (2012) in order to fit the mid-IR continuum.…”
Section: Temperature and Density Structurementioning
confidence: 99%
“…In a recent study (González-Alfonso et al 2012, hereafter Paper I), we have reported on the Herschel/PACS observations of these two sources in H 2 O, H 18 2 O, OH, 18 OH, HCN, and NH 3 , together with a quantitative analysis in which a deconvolution of the continuum into several components enabled us to derive the column densities and abundances of these species associated with each of the components. A chemical dichotomy was found in Paper I: on the one hand, the nuclear regions of both galaxies have high H 2 O abundances (∼10 −5 ), and high HCN and NH 3 column densities, indicating a chemistry characterized by high T gas , T dust , and high density, where the release of molecules from grain mantles to the gas phase has occurred (through evaporation in "hot core" chemistry and sputtering in shocks).…”
Section: Introductionmentioning
confidence: 99%